Advances in assessing Sabellaria spinulosa reefs for ongoing monitoring. Issue 15 (12th July 2018) - Jenkins, Christopher; Eggleton, Jacqueline; Barry, Jon; O'Connor, Joey
Abstract: Standardized and repeatable data acquisition and analyses are required to enable the mapping and condition monitoring of reefs within Marine Protected Areas (MPAs). Changes in habitat condition must be reliably identified and reported to best support evidence‐based management. Biogenic reefs in temperate waters, that is, hard matter created by living organisms and raised above the seabed, provide food and shelter for many plant and animal species. This article explores the feasibility of habitat mapping, using remote sensing datasets, as well as metrics for repeatable and suitable assessment of areas of Sabellaria spinulosa for their status as biogenic reef. Data were gathered within the North Norfolk Sandbanks and Saturn Reef candidate Special Area of Conservation/Site of Community Importance in the southern North Sea. Six study areas were identified as potential locations of biogenic reef using previously acquired data, and these were targeted for further investigation using a combination of high resolution multibeam echosounder and sidescan sonar. Where potential S. spinulosa was identified from the acoustic data, a drop‐down camera system was employed for visual verification. Areas of known and potential S. spinulosa reef were mapped successfully at two of the six study areas, although future approaches should take careful consideration of the seabed morphology and predominant habitat backdrop to successfully interpret such data. Camera tows from S. spinulosa reef areas were broken up into 5‐s segments, with each segment scored for (a) average tube elevation; (b) average percentage cover; and (c) for the presence or absence of S. spinulosa . These metrics were utilized to create summary statistics, including a value of patchiness derived from presence/absence data, that is recommended for application as part of future monitoring programs. The application of this methodology could benefit wider assessments of similar threated or declining habitats such as intertidal Mytilus edulis beds on mixed and sandy sediments, Maerl beds, Modioulus modiolus beds, Ostrea edulis beds, and Zostera beds where patchiness may also be considered of environmental importance. Abstract : Our work looks to further explore subtidal mapping and analysis of the Ross Worm Sabellaria spinulosa with specific interest in development of a patchiness score from drop‐down video analysis. Our data were collected within an Marine Protected Area, specifically the North Norfolk Sandbanks and Saturn Reef Special Area of Conservation/Site of Community Importance, and makes strong links to the continued and developing need for evidence to support management and conservation decision making.